Creation of a Virtual Technology Laboratory and Organization of Training for Highly Qualified Personnel - V. A. Nemtinov; I. M. Manaenkov; Yu. V. Nemtinova (Moscow Polytechnic University, 2020)
The article describes the technology of virtual modeling which is used as a tool to improve the quality of engineering education. The authors propose an approach to the creation of a virtual technological laboratory prototype for studying the processes of organic dyes production in vAcademia software environment. The basic programming environment vAcademia was used to create the laboratory. To create the elements of the laboratory, the tools of various systems were used such as two- and three-dimensional design systems SketchUp, AutoCAD, COMPASS-3D; graphic and video editors: Adobe Photoshop, the GIMP, Photoscape, Windows Movie Maker, SONY Vegas Pro; visual simulation tool for dynamic systems SIMUL8; software for working with tables and text Microsoft Office. The virtual laboratory was created in order to simulate the real laboratory environment and the processes produced in it, as well as to simulate the learning environment in which students transform their theoretical knowledge into practical skills. The test researches on an assessment of the quality of education, with use of the developed communicative and educational environment in the form of virtual space of technological laboratory on studying of processes of production of organic dyes, showed its increase by 15,6%.